2017
DOI: 10.5604/01.3001.0010.0290
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Mortality and Resource Utilization in Viral Hepatitis Related Hepatocellular Carcinoma

Abstract: The rate of viral hepatitis-related HCC is increasing. Mortality and resource utilization related to HBV and HCV-related HCC is substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Indeed, our data showed that in 2005‐2016, compared to HCV‐negative HD recipients, HCV‐positive HD recipients had more of both outpatient and inpatient claims and longer inpatient hospitalization. In this context, the impact of HCV to resource utilization was previously reported and it is not dramatically different from that seen in the HD population. On the other hand, it is plausible that the chance of being identified as HCV positive may increase with receiving more episodes of care, which could also contribute to the reported differences in the resource utilization rates.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, our data showed that in 2005‐2016, compared to HCV‐negative HD recipients, HCV‐positive HD recipients had more of both outpatient and inpatient claims and longer inpatient hospitalization. In this context, the impact of HCV to resource utilization was previously reported and it is not dramatically different from that seen in the HD population. On the other hand, it is plausible that the chance of being identified as HCV positive may increase with receiving more episodes of care, which could also contribute to the reported differences in the resource utilization rates.…”
Section: Discussionmentioning
confidence: 63%
“…In fact, nonalcoholic steatohepatitis (NASH) as an indication for LT has risen substantially so that it is currently the second most common indication for LT in the US, [ 5 , 6 ] synchronously with a steady increase in the prevalence of nonalcoholic fatty liver disease (NAFLD) and its complications in the US. [ 1 4 ] This trend is also affected by a simultaneous decrease in the number of patients with HCV requiring LT because of highly effective and safe antiviral treatments for HCV infection, [ 7 9 ] while no similarly effective treatment option exists for NAFLD. In fact, it is predicted that the combination of these 2 factors could push NASH or the progressive form of NAFLD, to become the most common indication for LT in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…CHB can cause cirrhosis, hepatocellular carcinoma, liver failure, and death. CHB is also associated with extra‐hepatic manifestations, decreased quality of life, and increased economic burden . As such, the 69th World Health Assembly approved the Global Health Sector Strategy to eliminate viral hepatitis by 2030…”
mentioning
confidence: 99%